Role of Early Elective Cholecystectomy in Acute Mild-To-Moderate Biliary Pancreatitis - Siddique, Muhammad Umar; Wattoo, Nasir Mehmud; Hira; Khan, Tayyaba Mushtaq; Muhammad Naeem; Adil Maqbool (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the outcomes of early versus delayed laparoscopic cholecystectomy (LC) in patients with mild/moderate acute biliary pancreatitis (ABP). Study Design: Prospective comparative study. Place and Duration of Study: General Surgery Department of Pak-Emirates Military Hospital, Rawalpindi, Pakistan, from Jun 23 to Feb 24. Methodology: The target population included patients who were diagnosed with mild/moderate ABP. 138 participants were distributed equally into two groups:(1) Early LC Group (2) Delayed LC Group. Both groups were compared in terms of operation timing, operative difficulty, intra/post-operative complications, conversion to open cholecystectomy, mortality, total length of stay (LOS) in the hospital, and recurrent biliary events (RBEs). Results: Mean LOS (days)in Early LC Group was 6.5±1.1 and in the Delayed LC Group was 9.7±1.8(p-value<0.001). No RBE occurred in Early LC Group, however, 15 patients in Delayed LC Group had RBEs (p-value<0.001). No statistically significant difference was observed between the two groups in terms of operative difficulty, intra/post-operative complications, and conversion to open cholecystectomy. Conclusion: Early LC done for mild/moderate ABP is associated with reduced total LOS in the hospital and no RBEs. There was no statistically significant difference observed between Early LC and Delayed LC in terms of operative difficulty, intra/post-operative complications, and conversion to open cholecystectomy.